PENGARUH KARAKTERISTIK FISIK DAN LOKASI PROPERTI RUKO TERHADAP HARGA RUKO DI KECAMATAN BOGOR TENGAH, 2014 - SURYANATA M, SOFWAN ([Yogyakarta] : Universitas Gadjah Mada, 2015)
This research is to analyze influence characteristic of physical and location of property shop-house on the price shop-house at sub-district of middle Bogor, bogor. Variable characteristic of physical covering a total building, the extent of land, and the building age. Variable of shop-house location, including distance from shophouse to CBD, distance from shop-house to the botanical gardens Bogor, distance from shop-house in museum Etnobotani, distance from shop-house to college, and distance of shop-house to train station. Use of data primary in research is obtained by way of spreading quistionnare to homeowners store kencana, located in the Surya Kencana street, Sudirman street, Paledang street, Dewi Sartika street, Merdeka street, Sawojajar street, GedongSawah street, RE Martadinata street, and Ciwaringin street at the sub-district of middle Bogor.This study using data cross section by using simple method random sampling and acquired 50 samples. The analysis used in this research is linear regression analysis and statistical analyses descriptive. The research in descriptive indicate the average price of shop-house Rp2.400.000.000 with the lowest price shop-house Rp1.800.000.000 and the highest prices shop-house Rp3.500.000.000. Average building area is 134 square meters with building wide smallest 100 square meters and building wide largest 190 square meters.The regression analysis showing variable characteristic of physical shophouse building size, land size of shop-house, and the building age influential positive and significant on the shop-house price.Variable location distance from shop-house to CBD, distance from shop-house to the botanical gardens Bogor, and distance of railway station have negative effects and significantly to shop-house.Variable location the distance from shop-house to museum etnobotani and distance of shophouse to college influential positive and significant the price shop-house. Keywords: The shop-house price, building size, land size, the bulding age, the distance from shop-house to CBD, distance to Bogor botanical garden, distance to Etnobotani museum, distance to college, distance to railway station